FORMIONG HIGHER-EDUTATION STUDENTS RESEARCH COMPETENCE (Archive of Conferences, 2021)
In this article, in the psychological literature, creativity is defined as “the creative abilities (abilities) of a person, thinking, emotions, communication, manifestation in certain types of competence, characteristics of the personality as a whole or its individual aspects